1977
DOI: 10.1007/bf01541127
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of professionally employed lesbians and heterosexual women on the MMPI

Abstract: The hypothesis tested is whether lesbianism implies psychopathology. The MMPI was given to 26 nonpatient lesbians who were professionally employed full time, and the results were compared to those for a group of 29 similarly employed heterosexual women. With the exception of the Sc scale, no difference was found on the clinical scales. The lesbian group achieved a significantly higher elevation than the nonlesbians on the Mf and Sc scales. Further analysis of the data on the Sc subscales indicated no differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The research on lesbian gender identity and gender role indicates greater or comparable masculinity and comparable femininity in lesbian women compared to hetersexual women (Adelman, 1977;Bell & Weinberg, 1978;Heilbrun & Thompson, 1977;Saghir & Robins, 1973;Ward, 1974). Again, based on role modeling theory, it was hypothesized that daughters of lesbian mothers would achieve higher masculinity and/or androgyny scores than daughters of heterosexual mothers.…”
Section: Discussionmentioning
confidence: 96%
“…The research on lesbian gender identity and gender role indicates greater or comparable masculinity and comparable femininity in lesbian women compared to hetersexual women (Adelman, 1977;Bell & Weinberg, 1978;Heilbrun & Thompson, 1977;Saghir & Robins, 1973;Ward, 1974). Again, based on role modeling theory, it was hypothesized that daughters of lesbian mothers would achieve higher masculinity and/or androgyny scores than daughters of heterosexual mothers.…”
Section: Discussionmentioning
confidence: 96%
“…In the main, these were studies exploring psychological adjustment (e.g. Adelman, 1977;Oberstone & Sukoneck, 1976), and quality of lesbian relationships (Peplau et al, 1978). Overwhelmingly, the findings of these studies suggested that lesbians were well adjusted and satisfied with their relationships, and, contrary to popular belief, were fully functioning members of society (e.g.…”
Section: Historymentioning
confidence: 94%
“…Depression is the most common form of psychopathology in non-patient female homosexuals, followed by anxiety states (Kenyon, 1968). Professionally-employed homosexual women who were neither members of a homophile organization nor psychiatric patients were recently studied by Adelman (1977). (The socioeconomic bias in this latter sample is readily evident).…”
Section: Intervention To Prevent Future Secondary Psychological Maladmentioning
confidence: 99%